Membangun Jiwa Entrepreneurship Pada Mahasiswa Melalui Pembelajaran Kewirausahaan (Studi Kasus Di Stai Daruttaqwa Gresik) - Warti’ah , Achmad Anwar Abidin (ACTIVA: Jurnal Ekonomi Syariah, 2018)
Growing the entrepreneurial spirit through entrepreneurial learning becomes the task of universities in preparing graduates who have an entrepreneurial spirit. Students are expected to have the ability in thinking to become entrepreneurs so as to create their own jobs, but it can also be used as a side job that can increase revenue.This study aims to find out in depth how to build entrepreneurship spirit in students through entrepreneurship learning in Islamic High School (STAI) Daruttaqwa Gresik.The method used is case study, through data collection related to entrepreneurial learning process. The result of research stated that STAI Daruttaqwa in building entrepreneurship spirit to students apply the theory learning and laboratory learning.Theoretical learning is done by the lecturers of entrepreneurship lecture subjects through classroom learning, followed by the assignment to make the textbook according to the topic given by the lecturer of the lecturers who are divided into groups.Each group must present its tasks to know the ability to master the entrepreneurial material. The learning of the laboratory is done by the lecturers of entrepreneurship lecture subjects through learning in making the products presented in the classroom and the students also participate in the making.Besides, students are also required to create business plans to create innovative products that are presented in the classroom so that all students can understand the entrepreneurial materials both theory and practice. With entrepreneurial learning in theory and laboratory learning is expected to change the mindset of students about the importance of entrepreneurial learning for students to be stocked after graduating back to live in the community. Keywords: Entrepreneurship, Entrepreneurship Learning, entrepreneurial spirit